Illocutionary act analysis on Everything Everywhere All at Once (2022) - Putri, Miranda Rosalina Ramadi (Passage: Journal of English Language and Literature, 2025)
The present study aims to describe and analyze the type of illocutionary act in the Everything Everywhere All at Once film using the theory proposed by Searle (1985 2005) and other relevant previous studies. The data were taken from the film and its script. After the data were categorized based on its type, the researcher tried to learn its context using the Hymes S-P-E-A-K-I-N-G model (2001) so the researcher could finalize its categorization more clearly. The study discovered four out of five types of illocutionary acts namely assertive (526 occurrences), directive (444 occurrences), expressive (69 occurrences), and commissive (30 occurrences). The findings in general can be used to help define the role, goal, or personality of some characters in the film/movie. The researcher found that the number and the context of the findings of the characters in the film can occur due to the influence of the characters' roles, personalities, or goals.